Corporate Governance Practices And Firm Performance: A Review And Interrogation Of Theory - Barante, Daniel M.; Arasa, Robert (International Journal of Innovative Research and Advanced Studies (IJIRAS), 2018)
This paper reviews literature on corporate governance practices with a focus on banking institutions, and their impact on the performance of these institutions. As such it contributes to the debate on the importance of corporate governance for firms across various sectors. Corporate scandals in the 1990s and 2000s drew the attention of governments to the importance of corporate governance, and induced legislation to prevent similar situations in the future. This paper reviews and interrogates theories that attempt to explain the concept of corporate governance. Based on the synthesis of the theoretical review, a blended model for on corporate governance is suggested. From the literature review done, it is seen that the nature and conduct of corporate behavior has implications on the level of corporate governance effectiveness in terms of transparency, accountability and sustainability which again has implications on firm competitiveness and relevancy. One of the key areas pointed out in the discussion of this paper is the silence by the postulators of the various theories on other forces that may bring about either facilitate or hinder the expected good corporate governance practices. The review and interrogation of theories further reveal that no one single theory can adequately explain the concept of corporate governance. Hence, we have suggested a blended approach to understanding corporate governance practices and also taking into recognition that there could be other forces that may moderate the nature and direction of corporate governance practices and effectiveness. Borrowing from the theoretical postulations, a model on corporate governance has been suggested.
Keywords: corporate governance